Mekong River Family within 21st Century Context: ครอบครัวลุ่มน้ำโขงกับบริบทความเปลี่ยนแปลงในศตวรรษที่ 21 - ต้นประดู่ ยุทธพงษ์ (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2018)
Globalization is changing rapidly As a result, the Mekong basin countries have to change policies and guidelines by setting policies. Get out of the loop 3 trap that hinders the development of the countries. Include 1) Medium Income Trap 2) Trapping inequality 3) Trap the developmental imbalance if the Mekong Basin countries through this trap. From countries in "developing countries" will change to "Developed countries" Therefore, it is necessary to accelerate the development of human resources to create knowledge rather than to accumulate knowledge. To upgrade the economy with the dimension of cultural diversity combined with modern technology Including lifestyle changes through direct experience. Indirect and create a new perspective and innovation the 4 dimensions are as follows. 1) Economic Wealth 2) Social Well-beings 3) Human Wisdom 4) Environmental Wellness The goal of the Mekong River Basin development group is to: Improving the quality of life of the Mekong population has improved quality of life Especially those who need to maximize their potential.The disadvantaged or those who are experiencing extreme poverty. So mission is important. Make this group "There is a social opportunity. Under uncertainty context. change Adaptation and not leaving behind Focusing on hedging against the Mekong River’s members, the trap of poverty by creating handicapping opportunities and integrating with the empowerment of the individual in the Mekong River. Especially the area will play a role the rules of the original world can’t be adapted to the new world trade. The lack of preparedness for global change and the establishment of a strategic link with ASEAN member countries members of the Mekong River Basin may lose their economic development opportunities or even trade disadvantages. The strengths of human resources in the MRB are diverse Biodiversity and cultural diversity. The rest should be filled with clear government policy. Good management with technology These have resulted in the Mekong countries being able to leap a lot further. The 4th Industrial Revolution (Industry 4.0)